1995
DOI: 10.1007/bf02368407
|View full text |Cite
|
Sign up to set email alerts
|

Diel vertical migrations ofMeganyctiphanes norvegica in the Kattegat: Comparison of net catches and measurements with Acoustic Doppler Current Profilers

Abstract: Diel vertical migration of a stable and well-defined population of Nordic krill, Meganyctiphanes norvegica {Crustacea, Euphausiacea) was investigated during eight days in August 1989, in the L~s6-Deep, East of the Danish island L~is6. Net catches with a multi-net (MOCNESS) and measurements with a moored and a shipboard Acoustic Doppler Current Profiler (ADCP) were compared. Backscattered energy as a measure for biomass gave good correlations to the dry weight of M. norvegica and smaller zooplankton from net ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Enright and Honeggar (1977) showed the occurrence and timing of migration of the copepod Calanus helgolandicus was not sensitive to a reduction in light level resulting from overcast weather conditions. In contrast, Buchholz et al (1995) showed that M. norvegica were well dispersed with depth on overcast days and were concentrated into discrete bands on clear days. A similar conclusion was drawn by Roe (1983) following a study of euphausiids in the northeastern Atlantic.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Enright and Honeggar (1977) showed the occurrence and timing of migration of the copepod Calanus helgolandicus was not sensitive to a reduction in light level resulting from overcast weather conditions. In contrast, Buchholz et al (1995) showed that M. norvegica were well dispersed with depth on overcast days and were concentrated into discrete bands on clear days. A similar conclusion was drawn by Roe (1983) following a study of euphausiids in the northeastern Atlantic.…”
Section: Discussionmentioning
confidence: 79%
“…M. norvegica has been observed, by means of an ADCP, to migrate from depths of 150 m to the surface at speeds of 0.02-0.03 m s-l (Buchholz et al 1995), while Frank and Widder (1997) report observing M. norvegica migrating at rates in excess of 0.1 m s-1. It has also been reported that both N. couchi (Williams and Fragopoulu 1985) and E. krohni (Roe et al 1984) have distinct migration cycles and are able to move vertically with speeds of 0.01-0.02 m s-1, although Williams and Lindley (1982) found no evidence of large-scale migration of T. longicaudata.…”
Section: Discussionmentioning
confidence: 99%
“…Mauchline 1980, Sameoto 1980, McClatchie 1985, Lass et al 2001. Although prey preference varies strongly with season and location (Lass et al 2001), the feeding mode of northern krill has been classified as opportunistic and non-selective (Mauchline 1980, Buchholz et al 1995, Lass et al 2001). However, Kaartvedt et al (2002) suggested that carnivorous feeding is performed selectively by visually hunting zooplankton, e.g.…”
Section: Feeding Ecologymentioning
confidence: 99%
“…Nordic krill Meganyctiphanes norvegica (M. Sars) undergoes a pronounced DVM throughout its geographical range (Sameoto 1980, Simmard et al 1986, Buchholz et al 1995, Onsrud & Kaartvedt 1998, Tarling et al 1998, Liljebladh & Thomasson 2001, a behaviour widely thought to result from a trade-off between securing food (surface layers) and reducing predation (deeper layers) (Banse 1964, Lampert 1989, Tarling et al 2000, Alonzo & Mangel 2001. This may necessitate traversing pycnoclines resulting in individuals periodically residing in bodies of water that may differ dramatically in their temperature, salinity and O 2 properties (Mauchline & Fisher 1969, Simmard et al 1986, Onsrud & Kaardvedt 1998, Spicer et al 1999.…”
Section: Introductionmentioning
confidence: 99%